2014
DOI: 10.1074/jbc.m114.550459
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquitin-specific Peptidase 20 Regulates Rad17 Stability, Checkpoint Kinase 1 Phosphorylation and DNA Repair by Homologous Recombination

Abstract: Background: Rad17 is a key DNA damage response protein that undergoes ubiquitylation-mediated degradation. Results: USP20 is a deubiquitylase that interacts with and stabilizes Rad17 in a proteasome-dependent manner, and it is required for Chk1 phosphorylation. Conclusion: USP20 is a novel regulator of the DNA damage response. Significance: USP20 role sheds more light on the ubiquitylation events associated with DNA damage, and may predict chemotherapy response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 21 publications
(24 reference statements)
0
27
0
Order By: Relevance
“…This is consistent with the observation by Shaheen et al. (31). Given that USP20 depletion-induced promotion of CHK1 activation is rescued by overexpression of CLASPIN (Figure 2H), CLASPIN is the major substrate for USP20 in CHK1 activation.…”
Section: Resultsmentioning
confidence: 99%
“…This is consistent with the observation by Shaheen et al. (31). Given that USP20 depletion-induced promotion of CHK1 activation is rescued by overexpression of CLASPIN (Figure 2H), CLASPIN is the major substrate for USP20 in CHK1 activation.…”
Section: Resultsmentioning
confidence: 99%
“…Currently, a study found that the high frequency of the 3-bp deletion in the USP20 gene in Korean population, which mean a biased susceptibility of Korean individuals to certain cancer types, and the potential mechanisms of carcinogenesis caused by mutant USP20 are still unknown (20). Furthermore, searching public databases of the Sanger Cosmic and the Cancer Genome Atlas, frequent point mutations and deletions of USP20 are found to exist in a variety of malignancies (13). Moreover, USP20 has been confirmed involved in various cellular mechanisms by impeding Tax- and interleukin 1p (IL-1p)-induced NF-κB activation by targeting Tax and TRAF6 for deubiquitination, which results in slower cell growth in ATL2 cells (14), enhancing HIF-1α-induced hypoxia response element (HRE) luciferase activity and VEGF protein expression via salvaging ubiquitinated HIF-1α from proteasomal degradation (12), and regulating β2 adrenergic receptor (β2AR) recycling and resensitization (21).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, USP20 has been confirmed involved in various cellular mechanisms by impeding Tax- and interleukin 1p (IL-1p)-induced NF-κB activation by targeting Tax and TRAF6 for deubiquitination, which results in slower cell growth in ATL2 cells (14), enhancing HIF-1α-induced hypoxia response element (HRE) luciferase activity and VEGF protein expression via salvaging ubiquitinated HIF-1α from proteasomal degradation (12), and regulating β2 adrenergic receptor (β2AR) recycling and resensitization (21). As Rad17 was implicated in carcinogenesis as a tumor suppresser gene that play a role in a haplo-insufficient manner (22), and USP20 stabilized Rad17 in a proteasome-dependent manner, USP20 itself was considered as a novel tumor suppressor protein (13). Additionally, USP20 could be ubiquitinated in a pVHL-dependent manner, inducing itself rapid degradation (23).…”
Section: Discussionmentioning
confidence: 99%
“…PKA-dependent phosphorylation of the DUB USP20 was recently shown to perturb post-endocytic trafficking of the β-andregenic receptor under cellular stress conditions. USP20 is implicated in control of the DNA damage response, cell cycling, and NF-κB activity 168, 169 , and its regulation by PKA links this kinase to control of DNA damage and NF-κB activity.…”
Section: Regulation By Alternative Splicingmentioning
confidence: 99%